Utility of Computer-based simulations in Experiments on Performance Assessment in Complex Task Environment: The GBE and operator Performance in Automated Ship's Bridge System - Mai Sumiyati, Ishak (Universiti Malaysia Sarawak, 1998)
Assessing subjective performance (i. e., mental workload, situation awareness, and stress) in a complex task environment has long been known as a difficult matter. Traditional participation observation and questionnaire method are not suitable in this case, for some reasons: 1) as it involves multiple tasks carried out at the same time where physical, biological, chemical and psychological cause-effect relationships among variables determining performance can only be identified using direct manipulation of those variables in the laboratory, 2) as participant observation and interview is dangerous, laborious and expensive, as in the case of ship's bridge, process control, spaceships, and aircraft systems; and 3) when the real environment is inaccessible, as in the case of the usability testing of the new design/product/systems. Simulation has been introduced to make a more effective experimental tool in this case. Concern has risen over the reliability of simulation as a tool to be used in performance assessmentin complex work environment This paper describes the use of ship's bridge simulation called GBE in assessing operator performance in navigation and collision avoidance tasks in complex ship's bridgework environment 58 participants were assigned to 3 kinds of simulation conditions: integrated, spatially separate and functionally separate ECDIS/ARPA systems. Participants were trained on navigation and collision avoidance tasks in 3 1.5-hr sessions, and were later tested for 4-5 hours. While they performed navigation & collision avoidance (as well as secondary tasks), they were faced with 16 scenarios consisting of 8 high complexity (emergency) and 8 low complexity (routine) collision scenarios. Measurements were taken on primary (navigation & collision avoidance) and secondary (cargo temperature recording and oil checks) tasks as well as subjective elements such as mental workload, situation awareness and subjective strain. The findings were compared to the theory of compensatory regulations; a theory on how human cope with work demands in real complex task environment propagated by Hockey (1993,1996). The findings showed the existence of the same coping style in the subjects. This finding supports the utility of simulation in psychological experimentation.